Stress of Yoga doer and Yoga non doer Teachers - Ravindra M Ghoti (MultiTech Publisher, 2023)
The present study has been designed to investigate the mental health and stress of yoga doer and yoga non doer school teacher. The research was conducted over a sample of 120 school teacher including yoga doer and yoga non doer as well as male and female (30 yoga doer and 30 yoga non doer male teachers and 30 yoga doer and 30 yoga non doer female teacher). All the participants were administered the mental health inventory and stress inventory data was analyzed using‘t’ test. The results reported that there exists a significant difference in mental health among yoga doer and yoga non doer teacher both male and female. Yoga doer teacher have better mental health as compared to yoga non doer school teacher. Significance difference is also observed between yoga doer and yoga non doer school teacher as regarding to their level of stress score.